A look from the external school evaluation on school leadership in Portugal - Guerreiro, Helder; Duarte, María Leonor; Barata, Isabel (Avances en Supervisión Educativa, 2024)
The main objective of this article is to present the results of a study on schools, whose leadership is considered excellent in the scope of the external evaluation of schools. For this purpose, the Strong Points identified by the assessment teams relating to the domain Leadership and Management were analyzed, which encompasses three fields of analysis – Vision and Strategy, Leadership, Management. To better understand the results obtained, we also shared the understanding of leadership that underpins the External Evaluation framework. Although the school director is a leader, s/he is not the only one. At a school we can evaluate the leadership and performance of coordinators, teachers, students... because they all have their own space and opportunities to be leaders. We also have written about the most common leadership styles in schools, which complement and coexist in schools and can be adopted by multiple leaders.